2018
DOI: 10.1002/berj.3485
|View full text |Cite
|
Sign up to set email alerts
|

Awareness within local authorities in England of autism spectrum diagnoses of looked‐after children

Abstract: Educational outcomes for looked‐after children on the autism spectrum are significantly poorer than for autistic children not being looked‐after by their local authority (those ‘in care’), and poorer than for most other groups of children with special educational needs who are looked‐after in England. Such poor outcomes have led to calls for specific attention to be paid to the needs of autistic looked‐after children within the care of local authorities. There is also evidence that the numbers of autistic chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…However, some expressed concerns over misdiagnosis and overdiagnosis, prohibiting any further exploration into underlying trauma-related conditions; this is reflective of other research (Kentrou et al., 2019; Rodriguez et al, 2018). Conversely, research has found that LAC who present with trauma-related conditions may prohibit clinicians from exploring underlying behaviours that suggest an NDD (DeJong, 2010; Parsons, et al., 2019; Pinto, 2019). Placing the child’s needs at the centre of services was at the core of each participant’s response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some expressed concerns over misdiagnosis and overdiagnosis, prohibiting any further exploration into underlying trauma-related conditions; this is reflective of other research (Kentrou et al., 2019; Rodriguez et al, 2018). Conversely, research has found that LAC who present with trauma-related conditions may prohibit clinicians from exploring underlying behaviours that suggest an NDD (DeJong, 2010; Parsons, et al., 2019; Pinto, 2019). Placing the child’s needs at the centre of services was at the core of each participant’s response.…”
Section: Discussionmentioning
confidence: 99%
“…This trend is often attributed to varying factors such as improved diagnostic assessment tools and increased awareness and understanding of the conditions (Elsabbagh, et al., 2012; Song, et al., 2021a). Similarly, emerging research proposes that the prevalence of NDDs has increased in the LAC population but with higher prevalence rates compared with their peers (Parsons, at al., 2019; Willis, Dhakras and Cortese, 2017). Disconcertingly, higher rates of maltreatment have also been suggested to occur in children with an NDD (McDonnell, et al., 2019; Stern, et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It tends to generate much higher response rates than traditional consensual survey methods owing to the fact that authorities are legally obliged to respond to requests and, outside of certain exemptions, provide any requested information (Fowler et al , 2013; Savage and Hyde, 2014). As with the principles of FoI legislation in general, research using FoI requests can also play an important democratic function, “both in terms of holding public authorities to account through making their workings more explicit and also … enabling wider participation of the public in research” (Parsons et al , 2019, p. 204).…”
Section: Methodsmentioning
confidence: 99%
“…We know from a plethora of studies that adverse early experiences can hugely impact a child’s developmental trajectory as they are associated with a multitude of negative developmental outcomes including mental health problems (Norman et al., 2012), lower academic achievement (McGuire and Jackson, 2018) and attachment problems (Baer and Martinez, 2006). Additionally, the complex question of causality aside, neurodevelopmental diagnoses such as attention-deficit/hyperactivity disorder or autism are overrepresented amongst children in care (Ogundele, 2020; Parsons et al., 2019). This ‘double jeopardy’ of trauma and neurodevelopmental conditions might pose additional risks to development (Gajwani and Minnis, 2023).…”
mentioning
confidence: 99%